Accessibility and Peripheries: An Empirical Investigation in the Lombardy Region - Flora Pagetti; Daniele Ietri; Paolo Molinari (Bollettino della Società Geografica Italiana, 2020)
This paper is related to a national research project covering every Italian region and province with respect to their performances in the attainment of the priorities of the 2014-2020 EU Cohesion Policy. The first part of the paper presents a survey of the literature available on Inner Peripheries, with specific regard to the methodologies useful for their identification. The second part will present an analysis at the national level, with a focus on the case of Lombardy, and an index of multimodal accessibility selected for a preliminary evaluation of the concept of Inner Periphery. The third part of the paper will discuss an empirical assessment of the Inner Periphery individuated in the Lombardy region, using a set of indicators provided by the STeMA model. The discussion developed in the three sections is intended to test the territories defined as Inner Periphery in Lombardy according to the set of indicators made available by the national project.